2013
DOI: 10.1155/2013/745159
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Ripening in The Netherlands: A Survey

Abstract: Objective. We aim to investigate methods and use of cervical ripening in women without and with a prior cesarean delivery in The Netherlands. Methods. In 2010, we conducted a postal survey in all Dutch hospitals with a labor ward. One gynecologist per hospital was addressed and was asked to respond on behalf of the staff. The questionnaire contained 31 questions concerning cervical ripening and induction of labor. We compared this survey to a similar Dutch survey conducted in 2006. Results. Response rate was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…showed that the most common ripening methods were used in very diverse ways, but they could not compared the methods at the individual level. 8,[15][16][17] To our knowledge, a single observational study, conducted in the United States and published in 2016, has compared these methods in current practice. 18 This comparison of 331 women found that the cost-effectiveness of misoprostol as a 50-μg vaginal tablet was better than that of the dinoprostone pessary.…”
Section: Data From Declarative Surveys About Maternity Units Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that the most common ripening methods were used in very diverse ways, but they could not compared the methods at the individual level. 8,[15][16][17] To our knowledge, a single observational study, conducted in the United States and published in 2016, has compared these methods in current practice. 18 This comparison of 331 women found that the cost-effectiveness of misoprostol as a 50-μg vaginal tablet was better than that of the dinoprostone pessary.…”
Section: Data From Declarative Surveys About Maternity Units Practicesmentioning
confidence: 99%
“…Data from declarative surveys about maternity units practices showed that the most common ripening methods were used in very diverse ways, but they could not compared the methods at the individual level . To our knowledge, a single observational study, conducted in the United States and published in 2016, has compared these methods in current practice .…”
Section: Introductionmentioning
confidence: 99%
“…A standard Foley catheter or a proprietary Cook cervical ripening balloon are the most commonly used mechanical methods of cervical ripening for the induction of labour . Because of the risks associated with pharmacological agents, the use of mechanical methods is on the rise in women with a previous caesarean section and other uterine scars …”
Section: Use Of Mechanical (Non‐pharmacological) Methods Of Inductionmentioning
confidence: 99%
“…41 Because of the risks associated with pharmacological agents, the use of mechanical methods is on the rise in women with a previous caesarean section and other uterine scars. 42 A 2012 Cochrane review that analysed 71 published randomised controlled trials (n=9722 women) reported similar vaginal delivery rates with lower risk of hyperstimulation with the use of mechanical methods than with other pharmacological methods for induction of labour. 41 Subgroup analysis of women with caesarean section or other uterine scars was not reported.…”
Section: Use Of Mechanical (Non-pharmacological) Methods Of Inductionmentioning
confidence: 99%
“…The amount of smooth muscle in the lower third of the cervix is estimated as 6.4%, in the middle third 18% and in the upper third 28.8%, but in the body of the uterus it is as high as 68.8%. In addition, the amount of actomyosin in the body of the uterus is significantly higher than in the cervix [13] and was shown to depend on the age and parity of the woman [14]. The cervix does not work as other sphincters in the body and expands passively and gradually.…”
Section: Embryological Considerationsmentioning
confidence: 99%